A novel locus (CORD12) for autosomal dominant cone-rod dystrophy on chromosome 2q24.2-2q33.1 - Meunier Isabelle; Bocquet Béatrice; Hebrard Maxime; Manes Gaël; Coustes-Chazalette Delphine; Sénéchal Audrey; Bolland-Augé Anne; Zelenika Diana; Hamel Christian P (BMC, 2011)
Abstract Background Rod-cone dystrophy, also known as retinitis pigmentosa (RP), and cone-rod dystrophy (CRD) are degenerative retinal dystrophies leading to blindness. To identify new genes responsible for these diseases, we have studied one large non consanguineous French family with autosomal dominant (ad) CRD. Methods Family members underwent detailed ophthalmological examination. Linkage analysis using microsatellite markers and a whole-genome SNP analysis with the use of Affymetrix 250 K SNP chips were performed. Five candidate genes within the candidate region were screened for mutations by direct sequencing. Results We first excluded the involvement of known adRP and adCRD genes in the family by genotyping and linkage analysis. Then, we undertook a whole-genome scan on 22 individuals in the family. The analysis revealed a 41.3-Mb locus on position 2q24.2-2q33.1. This locus was confirmed by linkage analysis with specific markers of this region. The maximum LOD score was 2.86 at θ = 0 for this locus. Five candidate genes, CERKL, BBS5, KLHL23, NEUROD1, and SF3B1 within this locus, were not mutated. Conclusion A novel locus for adCRD, named CORD12, has been mapped to chromosome 2q24.2-2q33.1 in a non consanguineous French family.